Use of the logarithmic decrement to assess the damping in oscillations - Montenegro Joo, Javier (2017)
A Virtual Lab to experimentally detect the frequency of the oscillations of a damped oscillator has been created. Once input data such as mass, elastic constant and damping of the medium are entered, the simu-lation module depicts the oscillations on computer screen, automatically detects the extreme displacements of oscillation and applies the logarithmic decrement algorithm, which leads to the exponent characterizing the gradual shrinking of displacements. From this exponent the frequency of the damped oscillations is calculated, this –as it is expected- is equal to its theoretically calculated value.